Environmental and genetic variation in leaf anatomy among populations of Andropogon gerardii (Poaceae) along a precipitation gradient - Olsen, Jacob T.; Caudle, Keri L.; Johnson, Loretta C.; Baer, Sara G.; Maricle, Brian R. (My University, 2013)
Premise of the study: Phenotypes of two Andropogon gerardii subspecies, big bluestem and sand bluestem, vary throughout the prairie ecosystem of North America. This study sought to determine the role of genetics and environment in driving adaptive variation of leaf structure in big bluestem and sand bluestem. Methods: Four populations of big bluestem and one population of sand bluestem were planted in common gardens at four sites across a precipitation gradient from western Kansas to southern Illinois. Internal leaf structure and trichome density of A. gerardii were examined by light microscopy to separate genetic and environmentally controlled traits. Leaf thickness, midrib thickness, bulliform cells, interveinal distance, vein size, and trichome density were quantified. Key results: At all planting sites, sand bluestem and the xeric population of A. gerardii had thicker leaves and fewer bulliform cells compared with mesic populations. Environment and genetic source population were both influential for leaf anatomy. Leaves from plants grown in mesic sites (Carbondale, Illinois and Manhattan, Kansas) had thicker midribs, larger veins, fewer trichomes, and a greater proportion of bulliform cells compared to plants grown in drier sites (Colby and Hays, Kansas). Conclusions: Water availability has driven adaptive variation in leaf structure in populations of A. gerardii, particularly between sand bluestem and big bluestem. Genetically based differences in leaves of A. gerardii indicate adaptive variation and evolutionary forces differentiating sand bluestem from big bluestem. Environmental responses of A. gerardii leaves suggest an ability to adjust to drought, even in populations adapted to mesic home environments.
Keywords: Adaptive variation; Andropogon gerardii; Big bluestem; Bulliform cells; Drought adaptation; Ecotypes; Leaf structure; Sand bluestem